Integration of STEAM Approach into Biology Education: Enhancing Learning and Critical Thinking - Novruzi Nurlana Azad (Advanced Journal of STEM Education, 2026)
The integration of STEAM (Science, Technology, Engineering, Arts, and Mathematics) principles into biology education has gained increasing attention in recent years as educators seek more innovative and effective approaches to enhance student learning outcomes. Biology, as a discipline that bridges both natural and applied sciences, provides a unique platform for implementing interdisciplinary strategies that stimulate curiosity and critical thinking. This study explores current pedagogical practices for applying STEAM principles in biology classrooms, with particular emphasis on interdisciplinary project-based learning, technology-supported laboratory activities, and inquiry-driven instruction. By incorporating creative elements and cross-curricular perspectives, STEAM-oriented approaches encourage students not only to acquire factual knowledge but also to develop transferable skills such as collaboration, communication, and problem-solving. Findings from this research indicate that integrating STEAM into biology instruction significantly improves student engagement, enhances conceptual understanding, and fosters innovative thinking, which are essential competencies in the 21st-century learning context. Furthermore, the study highlights practical recommendations for educators regarding curriculum design, resource allocation, and teacher professional development to ensure effective STEAM integration. The paper also identifies key limitations of the current study. It proposes directions for future research, particularly regarding the long-term impacts of STEAM-based biology instruction on academic achievement and career readiness.